A critical analysis of the taxation applicable to South African sports organisations - Heeger, Peter John (Department of Finance and Tax, 2017)
The study examined tax legislation that affects Public Benefit Organisations (PBOs) with specific emphasis on sports organisations. The relevance of the legislation was examined and secondly, where applicable, a review on how specific sports organisations (PBOs and recreational clubs) implemented the tax legislation was performed. A detailed analysis of the national and international sports environment was presented in order to inform the study. This was followed by a comprehensive examination of each section of the Income Tax Act in relation to PBOs and sport. A brief comparative study was also undertaken to benchmark South Africa against countries playing the same or similar sports. As the tax on Public Benefit Organisations is a relatively recent tax, little or no analysis has yet been conducted on its relevance and the implementation thereof. This study served to critically analyse the implementation of this tax by sports organisations using the limited data available in the public domain. The results revealed that the legislation is excessive, particularly for recreational clubs, taking into consideration South Africa's sporting development needs. In support of the findings, it is recommended that the Treasury consider separating the legislation affecting sports organisations from legislation affecting other Public Benefit Organisations.